Leukocytoclastic vasculitis and gastric adenocarcinoma - Mebazaa, Amel (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2010)
Background: Cutaneous vasculitis has been mainly associated with hematologic cancer. The association of solid neoplasms with cutaneous paraneoplastic vasculitis is rare. We report a case of cutaneous leucocytoclastic vasculitis that revealed a gastric adenocarcinoma. Case report: A 72-year-old man presented with an acute diffuse polymorphic eruption, with erythematous, vesicular, and necrotic lesions predominating on the lower limbs, which had developed within the past 8 days. The medical history revealed abdominal pain and weight loss over the previous 6 months. A skin biopsy noted typical leucocytoclastic vasculitis. A workup including GI tract investigations revealed an antral adenocarcinoma. Complete excision of the gastric tumor was followed by resolution of the skin lesions. No tumor recurrence or cutaneous vasculitis was noted during 2 years of follow-up. Conclusion: To our knowledge, the association of leucocytoclastic vasculitis with gastric cancer has never been reported previously. The failure of vasculitis to respond to conventional therapy should suggest an underlying malignancy.
Keywords: karcinom; kožne bolezni; vaskulitis